2017
DOI: 10.1007/s10753-017-0618-1
|View full text |Cite
|
Sign up to set email alerts
|

The Attenuation of 14-3-3ζ is Involved in the Caffeic Acid-Blocked Lipopolysaccharide-Stimulated Inflammatory Response in RAW264.7 Macrophages

Abstract: Inflammation plays important roles in the initiation and progress of many diseases. Caffeic acid (CaA) is a naturally occurring hydroxycinnamic acid derivative, which shows hypotoxicity and diverse biological functions, including anti-inflammation. The molecular mechanisms involved in the CaA-inhibited inflammatory response are very complex; generally, the down-regulated phosphorylation of such important transcriptional factors, for example, nuclear factor κB (NF-κB) and signal transducers and activators of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…F4/80 is a specific antigen for macrophages (36)(37)(38). iNOS is an important pro-inflammatory mediator expressed by macrophages under LPS induction (39)(40)(41). Thus, positive staining of both F4/80 and iNOS indicates macrophages are activated and are able to produce high levels of cytokines.…”
Section: Gent Attenuated M1 Type Macrophage Infiltration In Mouse Lunmentioning
confidence: 99%
“…F4/80 is a specific antigen for macrophages (36)(37)(38). iNOS is an important pro-inflammatory mediator expressed by macrophages under LPS induction (39)(40)(41). Thus, positive staining of both F4/80 and iNOS indicates macrophages are activated and are able to produce high levels of cytokines.…”
Section: Gent Attenuated M1 Type Macrophage Infiltration In Mouse Lunmentioning
confidence: 99%
“…To confirm the effect of NM on macrophage activation in the liver, double immunofluorescence staining was performed to label the M1-specific antigen F4/80 and iNOS in liver sections [ 31 ]. The results demonstrated abundant double-positive macrophages in the livers of septic mice, whereas NM reduced their presence ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that protocatechuic acid may inhibit the LPS-stimulated inflammatory mediator production in keratinocytes by reducing the Toll-like receptor-4-dependent activation of AKT, mTOR, and NF- κ B pathways and the activation of JNK and p38-MAPK [ 58 ]. Caffeic acid inhibited the inflammatory response by downregulating the phosphorylation of several important transcriptional factors, such as NF- κ B and STAT-3 [ 59 ]. In addition, vanillic acid inhibited the LPS-induced production of tumor necrosis factor TNF- α and interleukin IL-6 by suppressing the activation of NF- κ B and caspase-1 [ 60 ].…”
Section: Resultsmentioning
confidence: 99%